Mediating effect of psychological capital on the relationship between mental health literacy and coping styles among newly recruited nurses - Liyuan Xing; Ying Lu; Haixin Zhang; Zhiyi Shi; Shuying Chang; Weihua Liu; Jie Kou; Hongmei Zhang (BMC, 2024)
Abstract Background Newly recruited nurses face multiple sources of stress and their coping styles need to be focused on to ensure good mental health. This study aimed to examine the relationship among mental health literacy, psychological capital and coping styles in newly recruited nurses. Methods A cross-sectional study was conducted in August and September 2022. A total of 315 newly recruited nurses were recruited in a tertiary hospital in Henan Province, central China, employing the convenience sampling method. The self-reported questionnaires were sent through a QR code, including the Mental Health Literacy Scale for Healthcare Students, Psychological Capital Questionnaire, and Simplified Coping Style Questionnaire. Pearson correlation analysis was used to evaluate the relationships among the variables. Mediation analysis was performed to identify the mediating effect of psychological capital on the relationship between mental health literacy and coping styles. Results Positive coping showed a positive relationship with psychological capital and mental health literacy, while negative coping showed a negative relationship with psychological capital and mental health literacy. For positive coping, psychological capital was a partial mediator with an effect of 0.140, accounting for 62.8%. For negative coping, a full mediating effect was shown by psychological capital between mental health literacy and negative coping, with an indirect effect of -0.048. Conclusion Psychological capital plays a partial and complete mediating role between mental health literacy and different coping styles among newly recruited nurses. Diversified training and personalized guidance in improving mental health literacy and increasing psychological capital simultaneously can be provided to newly recruited nurses continuously to adjust their coping styles.